Preconditioning prefrontal connectivity using transcranial direct current stimulation and transcranial magnetic stimulation - Alkhasli, Isabel; Mottaghy, Felix M.; Binkofski, Ferdinand; Sakreida, Katrin (Frontiers in Human Neuroscience, 2022)
Transcranial direct current stimulation (tDCS) and transcranial magnetic stimulation (TMS) have been shown to modulate functional connectivity. Their specific effects seem to be dependent on the pre-existing neuronal state. We aimed to precondition frontal networks using tDCS and subsequently stimulate the left dorsolateral prefrontal cortex (lDLPFC) using TMS. Thirty healthy participants underwent excitatory, inhibitory, or sham tDCS for 10 min, as well as an excitatory intermittent theta-burst (iTBS) protocol (600 pulses, 190 s, 20 × 2-s trains), applied over the lDLPFC at 90% of the individual resting motor threshold. Functional connectivity was measured in three task-free resting state fMRI sessions, immediately before and after tDCS, as well as after iTBS. Testing the whole design did not yield any significant results. Analysis of the connectivity between the stimulation site and all other brain voxels, contrasting only the interaction effect between the experimental groups (excitatory vs. inhibitory) and the repeated measure (post-tDCS vs. post-TMS), revealed significantly affected voxels bilaterally in the anterior cingulate and paracingulate gyri, the caudate nuclei, the insula and operculum cortices, as well as the Heschl’s gyrus. Post-hoc ROI-to-ROI analyses between the significant clusters and the striatum showed post-tDCS, temporo-parietal-to-striatal and temporo-parietal-to-fronto-cingulate differences between the anodal and cathodal tDCSgroup, as well as post-TMS, striatal-to-temporo-parietal differences between the anodal and cathodal groups and frontostriatal and interhemispheric temporo-parietal cathodal-sham group differences. Excitatory iTBS to a tDCS-inhibited lDLPFC thus yielded more robust functional connectivity to various areas as compared to excitatory iTBS to a tDCS-enhanced DLPFC. Even considering reduced statistical power due to low subject numbers, results demonstrate complex, whole-brain stimulation effects. They are possibly facilitated by cortical homeostatic control mechanisms and show the feasibility of using tDCS to modulate subsequent TMS effects. This proof-of-principle study might stimulate further research into the principle of preconditioning that might be useful in the development of protocols using DLPFC as a stimulation site for the treatment of depression.